Pengaruh Kemutakhiran Teknologi, Partisipasi Pemakai, dan Dukungan Manajemen Terhadap Kinerja Keuangan Perusahaan - salsabila, salisa; Suwandi, Suwandi (Journal of Culture Accounting and Auditing, 2024)
This study aims to analyze technological sophistication, user participation, and management support on company financial performance. Furthermore, this study uses the effectiveness of accounting information systems as an intervening variable. The Structural Equation Modeling Partial Least Square (SEM-PLS) method was used by involving 50 employee respondents in companies engaged in construction services to test the influence between variables. The results showed that technological sophistication, user participation, and management support had no effect on financial performance, while accounting information systems showed a significant effect. Furthermore, accounting information systems are able to mediate the relationship between user participation and financial performance, but are unable to mediate the relationship between technological sophistication and management support. These findings underscore the importance of user involvement in the implementation of accounting information systems to improve financial performance. With this, companies need to increase the effectiveness of the use of accounting information systems by actively involving employee participation in company activities. Theoretically, this study enriches the literature on the effectiveness of accounting information systems and employee participation in improving the financial performance of companies.